LncRNA XIST promotes pancreatic cancer migration, invasion and EMT by sponging miR-429 to modulate ZEB1 expression. (August 2019) - Shen, Jie; Hong, Liang; Yu, Dan; Cao, Tietiu; Zhou, Zhengrong; He, Shengli
Abstract: Pancreatic cancer (PC) has become a worldwide malignancy accompanied by high metastasis and extremely poor prognosis. The critical roles of long non-coding RNAs (lncRNAs) in PC are generally summarized as molecular sponges of microRNAs (miRNAs). We intended to investigate the biological function and mechanism of lncRNA X-inactive specific transcript (XIST) in PC progression, especially in PC cell migration and invasion. qPCR was applied to detect the expression levels of XIST and miR-429 in PC tissues and cell lines. The roles of XIST and miR-429 on PC cell migration, invasion and epithelial-mesenchymal transition (EMT) were assessed by wound healing, transwell, qPCR and Western blot assays, respectively. The regulating relationship among XIST, miR-429 and zinc finger E-box binding homeobox 1 (ZEB1) was investigated in PC cells. XIST was frequently upregulated while miR-429 was commonly downregulated in PC tissues, especially in metastatic PC tissues. Knockdown of XIST in two PC cell lines caused inhibition of migration, invasion and EMT capacities. Forced expression of miR-429 exerted the similar tumor suppressing effects. XIST repressed miR-429 expression thus upregulated ZEB1, one of the targets of miR-429. ZEB1 mediated the tumor suppressing roles of XIST knockdown in PC cells. We identified the critical axis of XIST/miR-429/ZEB1 in PC cell migration, invasion and EMT, which may aid in developing new therapeutic strategies for PC.